Circulating miR‐99b‐5p as a novel predictor of erosion progression on high‐resolution peripheral quantitative computed tomography in early rheumatoid arthritis: A prospective cohort study. (4th July 2019) - Yue, Jiang; Lau, Terrence C. K.; Griffith, James F.; Xu, Jiankun; Xiao, Fan; Shi, Lin; Wang, Defeng; Wong, Priscilla C. H.; Li, Edmund K.; Tam, Lydia P.; Li, Martin; Li, Tena K.; et al.
Abstract: Objectives: To compare micro RNA (miRNA) expression: (a) between healthy individuals and early rheumatoid arthritis (ERA) patients with and without erosion on high‐resolution peripheral quantitative computed tomography (HR‐pQCT) at baseline; and (b) to explore whether these miRNAs could inform a signature predictive of erosion progression despite treatment with conventional synthetic disease‐modifying antirheumatic drugs (csDMARDs). Methods: The second metacarpophalangeal head (MCP2) was scanned by HR‐pQCT at baseline and 1 year in 117 ERA patients. We performed global profiling of 377 miRNAs in 10 ERA patients with and without erosion on HR‐pQCT at baseline and six healthy controls. Validation of the miRNAs of interest were conducted using TaqMan ® quantitative real‐time polymerase chain reaction in the validation ERA cohort (n = 117) at baseline. Correlation between the candidate miRNAs and erosion progression over 1 year were also assessed. Results: In the 377 screened miRNAs, 94 (60.6%) miRNAs were upregulated in patients with erosions, with 13 (8.4%) upregulated more than 2‐fold. Sixty‐one (39.4%) miRNAs were downregulated in patients with erosions, with 6 (3.9%) downregulated more than 2‐fold. Expression of miR‐143‐3p, miR‐145‐5p and miR‐99b‐5p were significantly higher in the plasma of ERA patients with erosions compared with those without erosions. Logistic regression analysis revealed that the baseline expression of miR‐99b‐5p was an independent predictor of erosion progression at month 12 (Exp [B] = 4.257, 95% CI 1.178‐15.386, P  = 0.027). Conclusions: Differential expressions of circulating miR‐143‐3p, miR‐145‐5p and miR‐99b‐5p in the plasma of ERA patients may characterize a severe form of the disease. MiR‐99b‐5p, in particular, may serve as a possible predictor for erosion progression.